SOCIALIZATION OF COUNSELING ON THE BENEFITS OF NONI FRUIT FOR HYPERTENSION PATIENTS - Dian Novianti; Pahla Widhiani; Wahyu Triono; Bastoni Bastoni; Devi Yuliananda; Fitri Dian Perwitasari (Jurnal Abdisci, 2024)
Hypertension or high blood pressure is a health problem that is increasingly encountered in Indonesia. Traditional medicine using natural ingredients, such as noni fruit (Morinda citrifolia), has long been used by the community as an alternative therapy. This community service activity aims to discuss the effectiveness of socialization and counseling regarding the use of noni fruit in helping lower blood pressure in hypertensive patients. The time and place of the event is August 20, 2024, in Lingsana Village with a total of 20 participants. Community service activities consist of:1. Material preparation, 2. Implementation: distribution of leaflets, lectures, and questions and answers, 3. Evaluation. Counseling about the benefits of noni fruit for hypertensive patients can increase public knowledge about this herbal treatment, which was previously tested by 62% and increased to 86%. However, to avoid side effects, paying attention to the dosage and how to use it is necessary.